Political history of Santa Fe since the democratic transition (1983-2020): contributions, lines of research and vacancies (Quinto Sol, 2021)
This work, grounded in the perspective of new political history, analyzes and systematizes the most relevant contributions from the social sciences to the knowledge of Santa Fe (Argentina) province’s recent history. We particularly focus on works that deal with the period that goes from the democratic transition to the present day (1983-2020), highlighting the most important lines of work, their contributions to the field and the observed vacancies. The article is organized around three central issues: the study of the province’s electoral and political systems; works dealing with the characteristics and interplay dynamics between political-partisan actors; and contributions regarding other social actors as they relate to the local political system. The purpose of our work is to present a complete and thorough outlook of the current knowledge available regarding Santa Fe’s recent political history.
Keywords: recent history; subnational politics